(untitled) (Agroindustrial Science, 2022)
This research was carried out with the purpose of knowing the effect of the vegetal cover with vicia (Vicia sativa) and the application of guano from islands in the fertility of the soil, height and yield of the cañihua (Chenopodium pallidicaule). A Completely Random Block Design was installed with four treatments and three repetitions: T1 (Cañihua Variety Cupi Sin Vicia), T2 (Cañihua Variety Cupi + guano de isla), T3 (Cañihua Variety Cupi + Vicia), T4 (Cañihua Variety Cupi + island guano + Vicia). The chemical content of the soil and agronomic parameters such as plant and yield were evaluated after harvest. The results were processed by ANVA analysis and multiple comparison test with a significance level of 5%. It was found that treatments T4 and T3 significantly increased the amount of nitrogen, phosphorus, and organic matter, as well as height and yield. A significant positive correlation was found between the variables yield with nitrogen organic matter and plant height. In conclusion, the vegetal cover with vicia and the application of guano from islands influence the increase in soil fertility, and the yield of the cañihua crop.